Environmental health in Mexico: Current situation and future prospects - Horacio Riojas-Rodríguez; Astrid Schilmann; Lizbeth López-Carrillo; Jacobo Finkelman (Salud Pública de México, 2013)
Environmental health has been established in Mexico as a discipline since the early nineties resuming the sanitarian tradition developed over the past century and incorporating new knowledge generated by environmental toxicology and epidemiology. During the last decade there has been some  progress in reviewing and updating the regulations, designing programs and policies to reduce exposure to pollutants and consolidating research groups and teaching in the area. However, the most prevalent problems previously diagnosed still remain and new risks have emerged due to environmental degradation (air pollution, toxics exposure and climate change among others) have been incorporated. If this trend persists, the environmental risks will continue to increase and multiply. The environmental health governance in Mexico has to be redesigned involving a transectoral approach. Future proposals  might include: establishment of a National Environmental Health Program, update the situational diagnosis at national and regional level, strengthening teaching and graduate programs in environmental health as well as increase support for research in the area and development of an integrated environmental health surveillance system.